О нулях функций, аналитических в полуплоскости, и полноте систем экспонент - Винницкий, Б.В. (Український математичний журнал, 1994)
Sequences of zeros are described for functions f analytic in the right halfplanc and satisfying the condition |f(z)| ≤ 0(1)exp(σ|z|), 0 ≤σ ≤ ∞ criterion of completeness of a system of exponentials in a space of functions analytic in a semistrip is established.